Effects of Gene Polymorphisms, Metabolic Activity, and Content of Alcohol Dehydrogenase and Acetaldehyde Dehydrogenases on Prognosis of Hepatocellular Carcinoma Patients - Gao, Na; Chen, Jingjing; Qi, Bing; Zhao, Tianyuan; Guo, Yuanyuan; Fang, Yan; Han, Zixinying; Qiao, Hai-ling (Turkish Journal of Gastroenterology, 2022)
Background: Alcohol dehydrogenase and acetaldehyde dehydrogenases have been associated with hepatocellular carcinoma, but how alcohol dehydrogenase and acetaldehyde dehydrogenases alter the prognosis of hepatocellular carcinoma have not been completely elucidated. Methods: Metabolic activities, gene polymorphisms, and content of alcohol dehydrogenase and acetaldehyde dehydrogenases were determined in 68 fibrotic livers from hepatocellular carcinoma patients. These characteristics were then correlated with clinical features and prognosis in these patients. Results: The median survival time of the ALDH-high activity group (727 days) was increased by 128% compared with that of ALDH-low activity group (319 days), and there was a significant negative correlation between the activity of acetaldehyde dehydrogenases and the level of alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase. There was no difference in survival time between ALDH2-high and ALDH2-low expression group, though the activity of acetaldehyde dehydrogenases had correlation with the content of ALDH2 (r = 0.6887, P < .001). Mutation at ALDH2rs671 significantly decreased both the activity and content of acetalde- hyde dehydrogenases, but the polymorphism had no relationship with progression of hepatocellular carcinoma patients. In addition, the activity and 3 polymorphisms of alcohol dehydrogenase had no effect on overall survival. Mutation at ADH1Crs698 significantly decreased both the activity and content of alcohol dehydrogenase (P < .05), mutation at ADH1C rs2241894 had an inverse effect, and mutation at ADH1B rs1229984 increased activity but did not affect content. The activity of alcohol dehydrogenase had a moderate cor- relation with the content of ADH1A and ADH1C in livers (P < .05). Conclusion: Low activity of acetaldehyde dehydrogenases in livers correlates with poor prognosis and clinical progression in hepatocel- lular carcinoma patients, and both gene polymorphisms and content influence its metabolic activity. Cite this article as: Gao N, Chen J, Qi B, et al. The effects of gene polymorphisms, metabolic activity, and content of alcohol dehydrogenase and acetaldehyde dehydrogenases on prognosis of hepatocellular carcinoma patients. Turk J Gastroenterol. 2022;33(7):606-614.